Development of Science Mobile Learning as an Innovation in Learning Media in Elementary Schools - Nuraini; Zul Hidayatullah; Laxmi Zahara; Nunung Ariandani (Jurnal Penelitian Pendidikan IPA, 2024)
Learning media innovation in the current era is starting to develop towards the use of technology. The learning media that is starting to develop today is mobile learning which can be installed on a smartphone. The use of mobile learning is inseparable from the rapid development and use of smartphones among students. Therefore, to reduce its negative impacts, it is necessary to develop mobile learning as a learning media so that students can use their smartphones to help the learning process. This study aims to develop valid and practical science mobile learning that can be used to help the science learning process at the elementary school level. This type of research is R&D with the ADDIE method. The location of the research is at Hamzanwadi University with the research subjects being science education and PGSD students at Hamzanwadi University. Analysis of research data using V'Aikens related to media validity and practicality analysis related to the practicality of learning media. The results of the analysis show that the developed science mobile learning is valid feasible and practical to use in the science learning process in elementary schools.